Histological study on the ovaries of Haemonchus contortus (Nematoda) - Jatinderpal Singh (International Journal of Life Sciences, 2017)
The didelphic female reproductive system in Haemonchus contortus possesses telogonic ovaries, each divisible into a germinal zone and a growth zone and are enveloped by a thin layer of squamous epithelium. Many cytoplasmic strands congregate in the formation of rachis in the germinative zone. The rachis acts as a supporting structure only and keeps the young gametocytes in position till these are mature for fertilization. In the growth zone, the ovaries are tightly coiled around the intestine suggesting the trans-membrane flow of nutrients from the later to the former.